What are integrated circuits? - Harris, Patricia, 1943 October 17- (2017)
Shares the history of integrated circuits, including who came up with the original idea, how integrated circuits changed electronics, and how they are designed.
Computer technology in daily life -- Before integrated circuits -- The idea is born -- Integrated circuits in the United States -- What's an integrated circuit? -- Designing integrated circuits -- Fabrication -- Moore's law -- What's to come? -- New advances.
Includes index.
8+
Keywords: Integrated circuits -- Juvenile literature